Alpha-actinin-3 R577X Polymorphism Profile of Turkish Professional Hip-Hop and Latin Dancers - ULUCAN, KORKUT (ANNALS APPLIED SPORT SCIENCE, 2016)
Actins are small globular filaments functioning in cell processes like muscle contraction, and stabilized to the sarcomeric Z-discs by actin binding proteins (actinins). One of the important gene coding for actin binding proteins in fast twitch fibers is alpha-actinin-3 (ACTN3). In this research, we have conducted a gene profile study investigating the genotype and allele distributions of ACTN3 R577X polymorphism in Turkish professional hip-hop and latin dancers and compared them to non-dancers as a control group. 30 professional dancers and non-dancers were recruited for the study. A genotyping procedure was carried out by a newly introduced four-primer PCR methodology. For statistical analysis, the Chi-square test was used to compare data between the groups (p<0,05 evaluated as significant). Numbers and the percentages of dancers were 2 (7%), 21 (70%) and 7(23%) for RR, RX and XX genotypes, respectively. The same numbers and the percentages were 15 (50%), 8 (15%) and 7 (23%) for RR, RX and XX genotypes, respectively, for the controls. Allele numbers and percentages of the R allele were 38 (63%) and 25 (42%) for the control and dancers, respectively. For X allele, the respective number for control and dancers were 22 (37%) and 35 (58%). No significant difference was detected between the groups in the terms of genotypes and alleles. Only RX genotype was significantly different between dancers and non-dancers (p<0,05). The results of the present and the first study, associating professional dancers and ACTN3 R577X polymorphism, is suggesting that RX genotype may have an genetic advantage for the physical predisposition for dancing, at least in the terms of ACTN3 R577X polymorphism. Prospective studies with extended numbers of dancers focusing on the influence of ACTN3 R577X polymorphism are required for confirmation of these findings.
Keywords: Athletic Performance; Dancer; Actinin; PCR; Sport Genetics; ACTN3 R577X; PERFORMANCE; GENOTYPE; GENE